Recurrent surgery in uterine prolapse: A nationwide register study - Malin Brunes; Ulrika Johannesson; Anna Drca; Ida Bergman; Marie Söderberg; Anna Warnqvist; Marion Ek (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction One in three women with pelvic organ prolapse (POP) undergoing surgery have a relapse. Currently, no optimal surgical treatment has been identified for correcting a uterine prolapse. This population‐based register study aims to compare the relapse rate in patients with uterine prolapse undergoing hysterectomy with suspension or uterine‐sparing surgical procedures. Material and methods All women with uterine prolapse undergoing prolapse surgery in Sweden from January 1, 2015 to December 31, 2018, were identified from the Gynecological Operation Register (GynOp). The primary outcome was the number of recurrent POP surgeries up to December 31, 2020. Results Sacrospinous hysteropexy (SSHP) without graft and sacrohysteropexy (SHP) were associated with a significantly higher rate of recurrent POP surgery (SSHP without graft: adjusted odds ratio [aOR] 2.6, 95% CI 2.0–3.5; SHP aOR 2.6, 95% CI 1.8–3.7) and patients describing a sense of globe (SSHP without graft, aOR 2.0, 95% CI 1.6–2.6; SHP, aOR 1.8, 95% CI 1.1–3.1) compared with cervical amputation with uterosacral ligament fixation (Manchester procedure). There was no difference in the reoperation rate or sense of a globe between SSHP with graft and Manchester procedure. Patients undergoing SSHP without graft had a higher frequency of 1‐year postoperative complications compared with Manchester procedure (aOR 2.0, 95% CI 1.6–2.6) and SHP (aOR 2.4, 95% CI 1.4–3.9). Moreover, the frequency of 1‐year postoperative complications was higher in SSHP with graft (aOR 1.6, 95% CI 1.1–2.2) than in Manchester procedure. Conclusions The Manchester procedure was associated with a low rate of recurrent POP surgery, symptomatic recurrence and low surgical morbidity compared with other surgical methods in women with uterine prolapse.